Protocol for AREST: Apixaban for Early Prevention of Recurrent Embolic Stroke and Hemorrhagic Transformation—A Randomized Controlled Trial of Early Anticoagulation After Acute Ischemic Stroke in Atrial Fibrillation - Rose, David Z.; Meriwether, John N.; Fradley, Michael G.; Renati, Swetha; Martin, Ryan C.; Kasprowicz, Thomas; Patel, Aarti; Mokin, Maxim; Murtagh, Ryan; Kip, Kevin; Bozeman, Andrea C.; McTigue, Tara; et al. (Frontiers in Neurology, 2019)
Background: Optimal timing to initiate anticoagulation after Acute Ischemic Stroke (AIS) from Atrial Fibrillation (AF) is currently unknown. Compared to other stroke etiologies, AF typically provokes larger infarct volumes and greater concern of hemorrhagic transformation, so seminal randomized trials waited weeks-to-months to begin anticoagulation after initial stroke. Subsequent data is limited and nonrandomized. Guidelines suggest anticoagulation initiation windows between 3 and 14 days post-stroke, with Class IIa recommendations, and level of evidence B in the USA and C in Europe. Aims: This open label, parallel-group, multi-center, randomized controlled trial AREST (Apixaban for Early Prevention of Recurrent Embolic Stroke and Hemorrhagic Transformation) is designed to evaluate the safety and efficacy of early anticoagulation, based on stroke size, secondary prevention of ischemic stroke, and risks of subsequent hemorrhagic transformation. Methods: Subjects are randomly assigned in a 1:1 ratio to receive early apixaban at day 0-3 for Transient Ischemic Attack (TIA), 3-5 for small-sized AIS (<1.5cm) and 7-9 for medium-sized AIS (1.5cm or greater, but less than a full cortical territory), or warfarin at 1 week post-TIA or 2 weeks post-stroke. Large AIS are excluded. Study outcomes: Primary: recurrent ischemic stroke, TIA, and fatal stroke; Secondary: Intracranial Hemorrhage (ICH); Hemorrhagic Transformation (HT) of ischemic stroke; Cerebral Microbleeds (CMB); Neurologic Disability (e.g., mRS, NIHSS, SS-QOL); and Cardiac Biomarkers (e.g., AF burden, TTE/TEE abnormalities). Sample size estimates: Enrollment goal was 120 for 80% power (2-sided type I error rate of 0.05) to detect an absolute risk reduction of 16.5% postulated to occur with apixaban in the primary composite outcome of fatal stroke/recurrent ischemic stroke/TIA within 180 days. Enrollment was suspended at 91 subjects in 2019 after a focused guideline update recommended Direct Oral Anticoagulants (DOACs) over warfarin in AF, excepting valvular disease (class I, level of evidence A). Discussion: AREST will offer randomized controlled trial data about timeliness and safety of anticoagulation in AIS patients with AF.